Development of advantus™(imidacloprid) soft chewable tablets for the treatment of Ctenocephalides felis infestations on dogs - Tariq Qureshi; William R. Everett; Kathleen G. Palma (Parasites & Vectors, 2015)
Abstract Background Studies reported here were conducted to evaluate the safety and effectiveness of advantus™ (imidacloprid) soft chewable tablets for the treatment of flea (Ctenocephalides felis) infestations on dogs and puppies 10 weeks of age or older and weighing 4 pounds or greater. Methods A pharmacokinetic study was conducted to evaluate parameters of orally administered imidacloprid. A dose confirmation study was conducted to confirm the efficacy of 0.75 mg/kg at 8, 12 or 24 hours post-treatment. A knockdown and speed of kill study was conducted to confirm the efficacy of 0.75 mg/kg dose at 0.5, 1, 4 or 24 hours post-treatment. The safety of a daily dose administered for six months at approximately 1, 3, and 5 times the maximum exposure dose of 3.75 mg/kg was evaluated in puppies. A field study was conducted to evaluate the safety and efficacy of a daily oral dose of 0.75 mg/kg for 14 days in client-owned dogs. Results The pharmacokinetic parameters of the final imidacloprid oral formulation were; Tmax 1.31 hours, Cmax 690.0 ng/mL, AUC 2615.5 h*ng/mL and half-life was 2.2 hours. The efficacy of 0.75 mg/kg BW was 98.6 %, 99.9 % and 100 % at 8, 12 and 24 hours post-treatment, respectively. The live flea counts were significantly different (p < 0.0001) and the treatment was well tolerated. The flea counts at 1 hour post-treatment were significantly lower in the treated group and the speed of kill efficacy was 96.6 % at 4 hours post-treatment in the knockdown and speed of kill study. The target animal safety study showed that the advantus™ soft chewable tablets administered orally to 10-week-old puppies once daily for 6 months at approximately 1, 3 and 5 times the maximum dose of 3.75 mg/kg was well tolerated and did not produce clinically relevant findings in Beagles. In the field study, efficacy of the soft chewable tablets administered daily for 14 days to flea-infested dogs was 98.2 %. Conclusion Imidacloprid administered orally as a soft chewable tablet for the treatment of fleas on dogs was safe and highly effective with a rapid knockdown effect and rapid elimination.